1987
DOI: 10.1901/jeab.1987.48-145
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Analysis of Choice on Concurrent‐chains Schedules

Abstract: Six pigeons responded on concurrent-chains schedules with either independent or interdependent equal variable-interval schedules in the initial links and unequal variable-interval schedules, always in a 2:1 ratio, in the terminal links. Relative response rates in the initial links increased across conditions as initial-link duration was shortened and decreased across conditions as terminal-link duration was shortened, replicating previous findings. Responses in the initial links were recorded in 5-s bins, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
20
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 17 publications
4
20
0
Order By: Relevance
“…Transient effects of reinforcement on subsequent responses have been observed in a number of other experiments on choice, but the effects of individual reinforcers are not always in the same direction. Fantino and Royalty (1987) reviewed the results of several studies of this type and presented some additional data from concurrent-chains schedules. They noted that positive recency effects have been found in studies that used concurrent schedules and an interdependent scheduling of reinforcers (e.g., Menlove, 1975;Morgan, 1974).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transient effects of reinforcement on subsequent responses have been observed in a number of other experiments on choice, but the effects of individual reinforcers are not always in the same direction. Fantino and Royalty (1987) reviewed the results of several studies of this type and presented some additional data from concurrent-chains schedules. They noted that positive recency effects have been found in studies that used concurrent schedules and an interdependent scheduling of reinforcers (e.g., Menlove, 1975;Morgan, 1974).…”
Section: Discussionmentioning
confidence: 99%
“…They noted that positive recency effects have been found in studies that used concurrent schedules and an interdependent scheduling of reinforcers (e.g., Menlove, 1975;Morgan, 1974). A negative recency effect (a transient decrease in the probability of a response on the same key) has been found in studies with concurrent-chains schedules and independent scheduling of reinforcers (e.g., Fantino & Royalty, 1987;Killeen, 1970). With other combinations (concurrent schedules with independent scheduling or concurrent-chains schedules with interdependent scheduling), neither positive nor negative recency effects have been observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have found the opposite: a negative recency effect, in which there was a lower response percentage on the alternative that had just delivered a reinforcer (Fantino & Royalty, 1987;Killeen, 1970). Fantino and Royalty proposed that negative recency effects are most likely to be seen when the initial links are two independent VI schedules, because immediately after a reinforcer is delivered for one alternative, the probability of reinforcement is temporarily increased for the opposite alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Such molar measures of responding provide the foundation for many modern theories of operant conditioning and have been particularly important in clarifying how animals process temporal cues and make response decisions during conditioning (for review, see Staddon & Cerutti, 2003). A minority of researchers has attempted to supplement this approach with more molecular measures of responding during learning (Blough, 1963;Fantino & Royalty, 1987;Newland, 1997;Palya, 1992;Shimp, 1992;Silva & Pear, 1995;Silva, Pear, Tait, & Forest, 1996;Weiss, 1970), and to use such measures to develop alternative theories of conditioning (Galbicka, 1992;Misak & Cleaveland, 2011;Shimp, 1966;Shimp, Fremouw, Ingebritsen, & Long, 1994;Tanno & Silberberg, 2012). For instance, Silva and Pear (1995) analyzed measures of pigeon's spatial trajectories as the birds learned to respond to fixed-time (FT) and fixed-interval (FI) reinforcement schedules and found that movement stereotypy varied as a function of when rewards were delivered and on whether rewards were contingent on pecking.…”
mentioning
confidence: 99%